De corpo objeto a corpo cena: quando a dor de um segredo carregado no tempo transformou-se em poética da cena - LACERDA, Suzi Cristina da Silva (2023)
This scientific article is a descriptive memorial of the creation process of the scene presented in the Actor's Dramaturgy class. The writing and scenic poetics depart from experiences lived by the author during her childhood and adolescence, experiences that left marks, many of them not visible, and which became art through the scene presented. To describe this process, the author uses concepts such as Eugênio Barba's score, Wlad Lima's actor's dramaturgy and Antonin Artaud's Theater of Cruelty.